1985
DOI: 10.1056/nejm198509123131105
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Use in Pregnancy

Abstract: With the increasing use of cocaine in the United States, there has been growing concern regarding its effects on the fetuses and neonates of pregnant cocaine abusers. Twenty-three cocaine-using women enrolled in a comprehensive perinatal-addiction program were divided into two groups: those using cocaine only and those using cocaine plus narcotics. These two groups were compared with a group of women who had used narcotics in the past and were maintained on methadone during pregnancy, and with a group of drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
135
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(146 citation statements)
references
References 13 publications
10
135
0
1
Order By: Relevance
“…Cocaine use has been linked to an increased incidence of spontaneous abortion, renal and limb abnormalities, prematurity and low birth weight [15,17,23]. Behavioural abnormalities in infants exposed to cocaine in-utero have also been described [4]. Intra-uterine growth retardation, craniofacial abnormalities and developmental delay are features of the fetal alcohol syndrome [13,14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine use has been linked to an increased incidence of spontaneous abortion, renal and limb abnormalities, prematurity and low birth weight [15,17,23]. Behavioural abnormalities in infants exposed to cocaine in-utero have also been described [4]. Intra-uterine growth retardation, craniofacial abnormalities and developmental delay are features of the fetal alcohol syndrome [13,14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although few, if any, of the available studies have thoroughly matched or controlled for confounding variables, several have chosen women from the same obstetrical population as the drug users to reflect a background with similar prenatal risk factors (e.g., socioeconomic status, maternal age, and parity; Bingo1 et al, 1987;Chasnoff, Burns, Schnoll, & Burns, 1985;Chasnoff, Griffith, MacGregor, Dirkes, & Burns, 1989;MacGregor et al, 1987;Matera, Warren, Moomjy, Fink, & Fox, 1990). These studies all reflect a poorer pregnancy outcome for the cocaine-using pregnant woman.…”
Section: Identification Of a N Appropria Te Comparison Groupmentioning
confidence: 99%
“…Commonly used secondary drugs include nicotine, alcohol, marijuana, and opiates (Frank et al, 1988;. Several problems exist in the studies reported to date: (1) studies have not taken into account other drug use (Chouteau et al, 1988); (2) secondary drug use was identified but not taken into account in data analysis (Dombrowski et al, 1991;Handler, Kistin, Davis, & F e d , 1991;MacGregor et al, 1987;Spence et al, 1991); and (3) comparison groups were chosen with similar secondary drug use patterns but sample size prohibited using appropriate statistical analyses to determine the impact of multiple drugs on outcome (Bingol et al, 1987;Chasnoff et al, 1985). Only a few studies have taken secondary drug use patterns into account in their analyses of outcome (Frank et al, 1990;McCalla et al, 1991;Zuckerman et al, 1989).…”
Section: Identification Of a N Appropria Te Comparison Groupmentioning
confidence: 99%
“…L. REv. 1011, ro67 n. 196 (1989). Coiker recognizes that the "physician's actions reflect the dominant sociai message -that a healthy (white) woman should wan t to bear a child ' ' I d .…”
Section: See Idmentioning
confidence: 99%